Sistem Informasi Administrasi Servis dan Penjualan Motor Honda pada CV Anugrah Jaya Sumenep - Lie Verry Erwan; Yulia Yulia; Silvia Rostianingsih (Jurnal Infra, 2018)
CV Anugrah Jaya is an authorized dealer of Honda in Sumenep. Sales system offered by the company are the service, sales of motorcycles and spare parts. Currently, CV Anugrah Jaya forced Honda center to apply information systems. An analysis and design with data flow diagrams and entity relation diagrams are performed before application development begins. This application is created using the programming language HTML, PHP, JavaScript, AJAX, MySQL database, and Bootstrap. The created application contains features of purchase orders for motorcycles and spare parts as well as sales of motorcycles, spare parts, and services The final result of the application development is the calculation of the price of spare parts on the stock card when the purchase, sale of motorcycles and spare parts and service generate sales report, revenue report, stock report, and profit and loss, reminder service and file maintenance based on service transaction period and motorcycle.